Psychological Determinants of Collective Action for Climate Justice: Insights From Semi-Structured Interviews and Content Analysis - Bührle, Hannah; Kimmerle, Joachim (Frontiers in Psychology, 2021)
Student initiatives for climate justice are driving forces in the climate change debate, but the psychological determinants of students’ engagement for climate justice have hardly been investigated so far. For this study, we posited student engagement for climate justice to be a form of collective action and analyzed psychological determinants of collective action as well as subjective processes of change in these determinants. For this purpose, semi-structured interviews were conducted with four individuals who were engaged in different student initiatives. The results of a qualitative content analysis showed that student collective action for climate justice as reported by the respondents reinforced some of the psychological conditions of collective action established in the literature, such as collective and participatory self-efficacy expectations and feelings of fear and anger. We also found, however, that (first-time) participation in collective action cannot be fully explained by those known predictors. A sense of responsibility, awareness of problems, and extrinsic motives such as social contact were also conducive to participation, whereas politicized collective identities did not play a significant role. Finally, we discuss the results against the background of existing theoretical considerations and outline implications for further psychological study of collective action.